Performance Improvement of Multicarrier Systems Using Wavelet Filter Banks. (2016) - Chunkath, Job; Arjun, S.S.; Sheeba, V.S.; Raj, S. Anso
Abstract: The need for higher data rates with increased bandwidth efficiency has focussed the search for techniques which deliver better results than conventional Orthogonal Frequency Division Multiplexing (OFDM) system. A wavelet filter bank system is investigated as a multicarrier modulation system (MCM). Such a system is found to be flexible, efficient and has many advantages over the present OFDM systems. This paper deals with identifying the suitability of different wavelet families, which can be used to improve the performance parameters of existing systems. Different wavelets families Daubechies, Meyer and Battle-Lemarie, are used as filter coefficients for wavelet based OFDM system and it is found that Daubechies wavelet (Db4) based multicarrier system outperforms the other two.